2013
DOI: 10.1007/s11096-012-9716-1
|View full text |Cite
|
Sign up to set email alerts
|

Patient perspectives on type 2 diabetes and medicine use during Ramadan among Pakistanis in Denmark

Abstract: For people with Muslim background and a chronic condition, fasting during Ramadan may mean changes in medicine use that are not always discussed with healthcare professionals. Healthcare professionals should acknowledge that Muslim patients may find fasting during Ramadan beneficial to their well-being and therefore choose to fast despite the Islamic rule of exemption. This patient-centred approach to counselling on medicines may facilitate better medicine use and thus better clinical health outcomes among pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 16 publications
2
58
0
Order By: Relevance
“…Additionally, fasting has been associated with a feeling of improvement in overall well-being, having a positive impact on social, cultural, and religious domains [28]. Health care professionals are seldom included in the spiritual decision as to whether or not a patient chooses to fast during Ramadan [27, 28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, fasting has been associated with a feeling of improvement in overall well-being, having a positive impact on social, cultural, and religious domains [28]. Health care professionals are seldom included in the spiritual decision as to whether or not a patient chooses to fast during Ramadan [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, fasting has been associated with a feeling of improvement in overall well-being, having a positive impact on social, cultural, and religious domains [28]. Health care professionals are seldom included in the spiritual decision as to whether or not a patient chooses to fast during Ramadan [27, 28]. The recent study by Gaborit and colleagues in France showed that many GPs had limited medical knowledge of Ramadan fasting in patients with diabetes, leading to over half of them proscribing fasting, even when it was not medically justified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Culturally insensitive recommendations were ineffective, in that, directing patients peremptorily not to fast did not appear to deflect vulnerable patients from still undertaking the fast [42]. Generally, patients may choose to ignore HCP advice, especially if they feel the HCP is not culturally attuned to their decisions [42, 46, 47]. In the case of Ramadan fasting, where religious beliefs strongly motivate patients to fast, HCPs (physicians and pharmacists) and religious sources, such as imams (Muslim religious priests), may need to collaborate as important sources of knowledge about fasting and medication use for patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, Danish studies among ethnic minorities have identified a high prevalence of medication-related problems in such patients, and also found that these problems could be identified, assessed and solved in collaboration between the patient, the community pharmacy and the general practitioner [14,15].…”
Section: Introductionmentioning
confidence: 99%